The interaction of central and peripheral processes in typing and handwriting: A direct comparison. - Cerni, Tania; Job, Remo (Journal of Experimental Psychology. Human Perception & Performance, 2022)
This study aimed to investigate the interaction between linguistic and peripheral-motor processes in written production. Past research has focused on this topic by analyzing how handwriting and, more recently, typing execution were influenced by lexical and sublexical variables. We took a step further in this study by directly comparing handwriting and typing, examining if different motor executions allow for different flows of linguistic processing. Participants typed and handwrote a set of Italian stimuli in which we manipulated lexicality (words vs. pseudowords), orthographic complexity (stimuli with vs. without multiletter graphemes), and length (short vs. long stimuli). We measured and analyzed latency (response times [RTs]), the difference between RTs and the acoustic duration (AD) of the stimuli (RT-AD), mean length of interletter intervals (ILIs), and whole response duration (WRD). We further explored the effects of the position of the orthographic complexity on RTs, RT-AD, ILIs, and WRD. Results suggested a cascaded, continuous processing flow for handwriting and a mixed mechanism involving both serial and parallel modes of processing for typing. The differences in linguistic processing during handwriting and typing suggest different mechanisms in segmenting, maintaining, and retrieving the orthographic representation during motor execution.